FOOD AND FEEDING HABIT OF DIFFERENT AGE GROUPS OF ASPIDOPARIA MORAR (HAM.) - GANDOTRA, ROOPMA; VIVEK, Mr.; SINGH, DALVINDER (Journal of the Inland Fisheries Society of India, 2021)
The study deals with the seasonal variations in natural diet, relative abundance of food items, Gastro somatic index (GSI) and Relative Gut Length (RGL) value of different age groups of Aspidoparia morar inhabiting river Tawi and its tributaries in Jammu region. The results revealed that the fish is mainly a herbi-omnivorous and euryphagic column feeder. The RGL value was observed to increase from 0+ age group (1.02) to 3+ age group (1.15) while GSI was maximum (4.41) in immature 0+ age group and decreased with increase in the fish length and age. Key words: Aspidoparia morar, food, feeding habits, Jammu